Ruptured peroneal aneurysm after infrapopliteal prosthetic bypass with Taylor patch. (2015) - Enzmann, Florian; Linni, Klaus; Hölzenbein, Thomas
Abstract: Introduction: A 45-year-old mailman underwent an implantation of a femoro-peroneal polytetrafluoroethylene (PTFE) bypass with a distal Taylor patch six years prior to admission after two failed autologous reconstructions and extensive fasciotomy. The initial pathology was an acute ischemia due to popliteal entrapment with subsequent popliteal thrombectomy. Report: The patient was examined because of pain, reduction of walking distance and development of a palpable mass at the medial fasciotomy site. A 6-cm pseudoaneurysm with complete disruption of the suture line of the vein patch was discovered and resected. Arterial continuity with a vein interposition graft was established using non-reversed cephalic vein. Conclusion: The etiology of the aneurysm is not entirely clear. One may argue that the fourth revascularization could have been performed with an arm vein instead of a prosthetic graft with the probability of a better long term patency in a young patient. 15 months after the procedure the bypass is patent and the patient is without any symptoms. This complication of a Taylor patch has not been reported before.